Homozygous sickle cell disease related mortality in Senegal (2011–2020). Issue 4 (4th October 2021) - Seck, Moussa; Ba, Oumou; Faye, Blaise Felix; Touré, Sokhna Aissatou; Guèye, Youssou Bamar; Dieng, Nata; Sall, Abibatou; Gadji, Macoura; Touré, Awa Oumar; Diop, Saliou
Abstract: Homozygous sickle cell disease (HSCD) is characterized by multiorgan morbidity and an increased risk of early death. We aim to describe the mortality rate, causes, and risk factors of death in HSCD between 2011 and 2020. We conducted a retrospective study with a duration of 10 years in the cohort of 2348 HSCD patients. The mortality rate was determined by reporting the number of deaths to the total number of patients followed in the year. Sociodemographic, clinical, biological data and causes of death were studied. Death risk factors were determined by a bivariate analysis comparing deceased and living HSCD patients. The mean age of death was 26 years (3–52). The sex ratio was 1.2. The mortality rate was 2.76%. The death rate was high in 2011 (3.2%) and low in 2020 (0.17%). We observed a significant reduction of mortality of 94.6%. Most of the common causes of death were acute anemia (40%), acute chest syndrome (24.6%), and infections (20%). Risk factors of death were age, vaso‐occlusive crises ≥3, acute chest syndrome, blood transfusion, and chronic complications. Mortality among HSCD has significantly decreased over the past 10 years in Senegal, and the main causes of death were acute anemia, acute chest syndrome, and infections.